The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.31258/jes.4.1.p.83-92
|View full text |Cite
|
Sign up to set email alerts
|

Development of Learning Tools with the Discovery Learning Model to Improve the Critical Thinking Ability of Mathematics

Abstract: This research was motivated by the still limited learning of mathematics as a means of supporting learning in the 2013 Curriculum. The purpose of this study was to produce some products in the form of learning devices (syllabus, RPP and LKPD) on the material for the flat side building of VIII Middle School with discovery learning models that meet valid, practical, and effective criteria for improving students mathematical critical thinking skills. Learning tools are developed using the 4-D model, which are def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 9 publications
0
11
0
9
Order By: Relevance
“…All learning activities must teach participants to be involved in the process of observation up to creation. It embodies discovery learning (Putri et al, 2020;Yerizon et al, 2018;Sulfemi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…All learning activities must teach participants to be involved in the process of observation up to creation. It embodies discovery learning (Putri et al, 2020;Yerizon et al, 2018;Sulfemi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…One of the models that can be used to solve the problem is the Discovery Learning model. Discovery learning is learning where ideas or ideas are conveyed through the discovery process (Putri et al, 2020;Zakaria and Syamaun, 2017). The learning process begins with providing stimulation, identifying problems, collecting data, processing and interpreting data, proving and drawing conclusions.Discovery learning is a method that encourages students to arrive at a conclusion based upon their own activities and observations.…”
Section: Introductionmentioning
confidence: 99%
“…22 of 2016 (Kartika et al, 2020). Furthermore, the learning tools made by the teachers still have weaknesses that must be repaired (Putri et al, 2020). Based on interviews with some mathematics teachers at high schools in Pekanbaru, it was found that some teachers only used learning tools, especially syllabus and lesson plans, which were obtained from other sources such as peers, the internet, etc.…”
mentioning
confidence: 99%